INFLUENCE OF DIFFERENT DRYING TECHNIQUES ON PHYSIOCHEMICAL AND NUTRITIONAL QUALITY OF MAIZE (Zea mays) GRAIN - SWGN, AMARASEKARA; JEMZIYA MB, FATHIMA; RIFATH MR, AHAMED (Innovare Journal of Agricultural Sciences, 2021)
Objectives: This study attempt to investigate the appropriate drying methods for post-harvest storage of maize grains with preserving important quality and physiochemical characteristics. Methods: The maize samples were dried using different drying methods such as field drying, greenhouse drying, solar drying, direct fire drying, hot air drying, and forced air drying. Further, the dried maize grains were analyzed for physical parameters of bulk density, particle density, porosity, specific gravity, shrinkage, and color. The proximate composition of dried maize grains was analyzed for crude protein, fiber, fat content, moisture, and ash content. Results: There were significant differences (p<0.05) observed for bulk density, particle density, porosity, specific gravity, shrinkage, and color between different drying techniques. When considering proximate analysis, protein, moisture, and ash content were shown significant differences (p<0.05) between different drying methods. Whereas, fat and fiber content of samples were not shown a significant difference (p>0.05) for different drying methods. Conclusion: Different drying methods affect the quality and physiochemical properties of maize grains. Among different drying techniques, the forced air oven drying method preserved physiochemical and nutritional properties considerably compared to other drying techniques.